Pengaruh Aplikasi PPA Kader terhadap Pengetahuan Kader tentang Deteksi Dini Stunting - Fika Kristi Febrina; Novita Rina Antarsih (Politeknik Kesehatan Kemenkes Mamuju, 2021)
Stunting is a growth disorder due to a lack of nutritional intake for a long time. Data from the World Health Organization (WHO), the prevalence of stunting in Indonesia is the third highest in Southeast Asia. The PPA Kader application is one solution in helping to overcome the stunting problem because cadres can get information on nutritional status assessments so fast and can detect stunting early. PPA Kader application for monitoring the growth is an android-based application based on the Z-Score value (BB/U, TB/U, BMI/U, and BB/TB), an imaginative and provocative medium for health education. To find out the effect of the PPA Kader application on the knowledge of village health workers about early stunting detection. This research was using pre-experimental research in one group pre-test post-test design. The research sample is 35 respondents taken from the village health worker population at the Integrated Services Post (Posyandu) in the area of the Public Health Center (Puskesmas) in Balik Bukit District with purposive sampling technique. This research was conducted from March to April. The intervention in this study was carried out using the PPA Kader application in which there was an educational explanation video about stunting. The data in this study were obtained through questionnaires that have been prepared for the pre-test and post-test to find out the knowledge of village health workers about early detection of stunting. Statistical test knowledge in this study is using Wilcoxon test. PPA Kader application can increase knowledge (p=0.000) of village health workers about early detection of stunting. The PPA Kader application affects the knowledge level of village health workers in the target area of the Balik Bukit District Health Center.